Sustainable Tourism and Ecosystem Conservation: Minimizing Impact on Fragile Ecosystems - O. C. Molua; A. O. Ukpene; T. N. Apaokueze; C. P. Ukpene; J. U. Emagbetere (Journal of Social Responsibility, Tourism and Hospitality, 2023)
Sustainable tourism is crucial in safeguarding the world’s fragile ecosystems. This article investigates the development and implementation of sustainable tourism practices to minimize the detrimental impact on these delicate environments. By studying the physics of ecosystem dynamics, the biology of local flora and fauna, and hospitality management techniques for eco-friendly tourism, we explore the vital connection between responsible tourism and ecosystem conservation. This research highlights the importance of striking a balance between tourism development and the protection of our natural heritage.